AB0490 Plasma Vitamin D Level in Primary Sjogren's Syndrome – Tunisian Comparative Study of 66 Patients. (15th July 2016) - Tougorti, M.; Kallel, A.; Ben fradj, M.K.; Ben Ghorbel, I.; Feki, M.; Riadh, J.; Houman, M.H.; Kaabechi, N.
Abstract : Background: Beyond its critical function in calcium homeostasis, vitamin D has recently been found to play an important role in the modulation of the immune/inflammation system. Increasing numbers of study have established that vitamin D insufficiency contributes to a number of diseases, suggesting a range of physiological functions of vitamin D. Recent findings seem to show that low vitamin D levels in patients with Sjogren Syndrom could be associated with severe complications such as peripheral neuropathy. Objectives: The purpose of this study was to evaluate plasma vitamin D level in Primary Sjogren's Syndrome (PSS) and comparing it with healthy controls. Methods: North Africans patients (Tunisian patients) with PSS were diagnosed in an internal medicine department. All patients with PSS meet the revised AECG criteria 2002 and/or ACR proposed criteria 2012. We proceed in this prospective study with a comparison of plasma vitamin D between two groups, with a matched age and sex, one of patients with a Primary Sjogren's Syndrome (PSS) and a second of healthy control subjects. Sixty six patients with PSS were enrolled. Sex ratio was 0.11 (59 female (89.4%) and 7 male (10.6%)).Mean age at diagnosis was 49.07 years ±12.56 (range 26 -73years). Forty eight healthy controls were included. Sex ratio was 0, 14 (42 females (87.5%) and 6 males (12.5%). Registration and statistical analysis of data were done with SPSS. Plasma 25-hydroxyvitamin D (25-OHD) concentrations were measured by a competitive chemiluminescence immunoassay using the Liaison Analyzer (DiaSorin Inc., Stillwater, MN). The inter-assay CV was below 10%. Vitamin D deficiency was defined according to the most recent cut-points defined by The Institute of Medicine as 25-OHD concentrations <10 μg/L. Results: Plasma vitamin D level of PSS patients was insufficient in 42.2% of cases (plasma vitamin D level <30 μg/L) and in 57.8% of cases plasma vitamin D level was lower than 10 μg/L. Plasma vitamin D was lower than 10 μg/L in 66.66% of healthy controls. There is no significant variation of plasma vitamin D levels according to sex, in the PSS group. Plasma vitamin D levels are not significantly decreased in patients with central and/or peripheral neurological manifestations compared to patients with no neurological symptoms. Plasma vitamin D levels are, however; significantly lower in male patients than controls. Conclusions: The incidence of vitamin D deficiency seems more important for PSS patients than healthy controls. It might be interesting to study these patients to examine the outcome of the disease and its severity after a vitamin D supplementation therapy. Disclosure of Interest: None declared